The utility of the 24-h delayed film of barium enema for detecting the dysganglionic bowel segment in Hirschsprung’s disease - Zhou, Bingyan; Wang, Di; Chen, Ke; Niu, Yonghua; Jiao, Chunlei; Zhu, Tianqi; Feng, Jiexiong (Frontiers in Pediatrics, 2022)
Background Preoperative evaluation of the dysganglionic bowel segment is critical for establishing the optimal resection strategy for Hirschsprung’s disease (HSCR), which facilitates patient outcomes. Objective We set out to determine the utility of the 24-h delayed film of barium retention in predicting the length of dysganglionic bowel segment in HSCR. Materials and methods A retrospective study of patients with clinically suspicious HSCR who underwent a preoperative 24-h delayed film of barium enema and were surgically treated from January 2015 to December 2019 was conducted. Results Two hundred and fifty-eight patients were enrolled in this study. The sensitivity, specificity, positive and negative predictive values of the 24-h delayed film of barium enema to predict the neuropathological segment were 89.1%, 91.5%, 91.3%, and 89.4%, respectively. The Youden index was 80.6%, with a kappa value of 0.806 (P < 0.001). The correlation rate between barium retention level and pathological results was 72.7% (16/22) when aganglionosis was restricted within the mid-distal rectum (short-segment type), increasing to 92.0% (46/50) and 93.5% (174/186) for patients that had aganglionosis extended beyond the mid-distal rectum (classical type) and sigmoid colon (long-segment type), respectively. Lastly, patients younger than 3 months showed a lower correlation rate (72.2%) compared to patients aged 3-12 months (91.0%) and > 12 months (92.6%). Conclusions Our investigation of the 24-h delayed film of barium enema performed for patients suspected of having HSCR indicated that the barium retention level remains crucial in predicting dysganglionic bowel segment, which contributes to the decision-making for surgical physicians.